Service Quality and Customer Satisfaction in the Hotel Industry - Nur Asyura, Muhamad (2010)
Common perception by practitioners in the hotel industry today that satisfied guest would become profitability to the company is considered as a major subject for this research. Therefore, this study is conducted to extend the previous research on the service quality by examining the relationship between service quality and customer's satisfaction. The importance of this study is to identify the factors that lead to guest's satisfaction and also proposing a method to assist hotel in identifying characteristics which will increase customer's satisfaction. In this research, the service quality is measured through perception of hotel guest and manager toward the service quality of three hotels located in Kota Bharu by using five dimensions of SERVQUAL (tangibles, reliability, responsiveness, assurance and empathy). There are also another two additional dimensions used which are food quality and reasonable price. On the other hand, the model gaps were also applied in order to identify the gaps between perception of hotel managers and guest (Gap 1) and between perceptions and expectation of customers (Gap 5) towards service quality of hotel. The hypotheses of this study supported that there are significant relationship between service quality and customer's satisfaction. Besides that, this study found that there is difference regarding perceptions between hotel manager and guest. However there is no difference for customers' perception and expectation regarding the hotel service except for two variables which are tangible and customer satisfaction.